Komunikasi dan Kepemimpinan Terhadap Kinerja Karyawan PT Enesis Group Batam - Irianti, Gina Nuraini; Sunargo (SCIENTIA JOURNAL, 2022)
Internal communication can be done in various ways by relying on telephone media, internet, whatsapp and so on, the need for communication between fellow employees even with the leadership. Good leadership and smooth internal communication are factors that affect employee performance. Assessing employee performance is important to know how far the organization's goals have been successfully realized. In this study sampling techniques using simple random sampling techniques and sample sizes in taking researchers' samples using the formula slovin. The data analysis methods used are descriptive analysis, data quality test, classical assumption test, multiple linear regression and hypothesis test with the help of spss. The results of data analysis are positive and significant communication on the performance of karyawan PT Enesis Group Batam with a result of t calculated value of 5,982 > t table 1,655. Leadership has a positive and significant influence on the karyawan of pt enesis group batam, with a t calculated value of 4,582 > t table 1,655. The results of the analysis of the influence of communication and leadership of pt enesis group batam prove that there is a positive influence between communication and leadership on employee performance. Communication and leadership simultaneously have a significant and close influence on employee performance.